2016
DOI: 10.1177/2168479015624732
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medical Mobile Applications Among Hospital Pharmacists in Malaysia

Abstract: The use of HHCs for DI among pharmacists in Malaysia was high. The use of locally produced DI sources is still low compared to overseas sources. The most popular applications used for drug-related medical information were Micromedex, followed by Lexicomp and Medscape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 411 publications
(17 citation statements)
references
References 29 publications
2
14
1
Order By: Relevance
“…Therefore, the actual response rate could be lower than reported here. The reporting rate was lower compared to another study conducted in Malaysia using an email survey form in which a response rate of 49.8% was reported among pharmacists in three Malaysian states [ 17 ]. Hence, future studies using this method of questionnaire distribution should be carefully considered in order to retrieve valid and accurate response rates.…”
Section: Discussioncontrasting
confidence: 59%
“…Therefore, the actual response rate could be lower than reported here. The reporting rate was lower compared to another study conducted in Malaysia using an email survey form in which a response rate of 49.8% was reported among pharmacists in three Malaysian states [ 17 ]. Hence, future studies using this method of questionnaire distribution should be carefully considered in order to retrieve valid and accurate response rates.…”
Section: Discussioncontrasting
confidence: 59%
“…Web-based survey was conducted through Lime-survey software. The survey instrument includes demographic characteristics (n=4 questions) and semi-structured questionnaire that was created based on studies in the literature to investigate knowledge and behaviours (n=5 questions), perception (n=8 questions) and point of view (n=4 questions) of pharmacy students towards mobile health apps [22,23,29,30]. The survey that include 20 items consisted of multiple sections, which are evaluated by using five-point Likert-type scales.…”
Section: Data Collection and Evaluationmentioning
confidence: 99%
“…Various studies [12][13][14][15][16] have shown that information and communication technology, particularly mobile devices, is used in all areas of health care, including drug dosage calculations. Currently, many people of different medical professions are using different mobile health applications and these have a positive effect on their activities and performance [15,17].…”
Section: Introductionmentioning
confidence: 99%